Combined DSEK and Transconjunctival Pars Plana Vitrectomy - Mona Sane; Naazli Shaikh; Saad Shaikh (Case Reports in Ophthalmological Medicine)
We report here three patients who underwent combined Descemet’s stripping with endothelial keratoplasty and transconjunctival pars plana vitrectomy for bullous keratopathy and posterior segment pathology. A surgical technique and case histories are described. Anatomic and visual outcomes of combined Descemet’s stripping with endothelial keratoplasty and vitrectomy were excellent. Our experience provides technical guidelines and limitations. The combined minimally invasive techniques allow for rapid anatomical recovery and return of function and visual acuity in a single sitting.